1991
DOI: 10.1088/0953-8984/3/11/004
|View full text |Cite
|
Sign up to set email alerts
|

Pre-transition softening and anomalous pressure dependence of shear constants in alkali and alkaline-earth metals due to band-structure effects

Abstract: Band-structure andshear-constant (C,,) calculations have been performed for the Li, Na and Ba BCC phase and the Cr, Ca and Sr BCC and FCC phases within a broad range of mmpressions(~fromOto40-55~.Todescribethe'baiidwntributionstoC,.,useismade of calculations based on the linear muffin-tin orbital/atomic sphere approximation (LMTO-ASA) method; the other contributions to C,. are described by using the semiempirical 'electrostatic' model. At U = 0 the calculated C,. values are usually close to the observed ones. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…However, this contribution is dominant only at a very low temperatures (typically of the order of 10 K or below), and phonon contribution should be considered. For acoustic phonons with small wave vectors, the Grüneisen parameter and thus the thermal expansion coefficient are proportional to hC ii /hu (typically there is only one shear modulus that is especially sensitive to the ETT, and it is the modulus that should be considered 51 ). Because 51 hC ii / dN(E F ), the low-temperature phonon thermal expansion coefficient is as singular as the electronic one.…”
Section: Letter Researchmentioning
confidence: 99%
“…However, this contribution is dominant only at a very low temperatures (typically of the order of 10 K or below), and phonon contribution should be considered. For acoustic phonons with small wave vectors, the Grüneisen parameter and thus the thermal expansion coefficient are proportional to hC ii /hu (typically there is only one shear modulus that is especially sensitive to the ETT, and it is the modulus that should be considered 51 ). Because 51 hC ii / dN(E F ), the low-temperature phonon thermal expansion coefficient is as singular as the electronic one.…”
Section: Letter Researchmentioning
confidence: 99%
“…Ca and Sr transform from fcc to bcc, and Ba from bcc to hcp, under pressure (Chen, Ho, and Harmon, 1988;Jona and Marcus, 2006;Qiu and Marcus, 2009). C 0 and C 44 in Ca, Sr, and Ba show sudden elastic variations and instabilities as a function of pressure (Vaks et al, 1991). Pollack et al (1997) found that the T ¼ 0 K low transverse [110] phonon branch becomes stabilized in bcc Be, Mg, Ca, Sr, and Ba under pressure.…”
Section: Appendix I: Pesudomorphic Epitaxymentioning
confidence: 99%
“…Initiated by the pioneering works of Hume-Rothery and Jones [97], this problem can be formulated in modern terms as how the proximity of a VHS to the Fermi level (E F ) and the ETT associated with it [98] affects the lattice structure, elastic moduli, phonon spectra, and other lattice properties. Numerous theoretical works devoted to this problem using both model [92,93] and ab initio [94,95] approaches have found (i) a considerable softening of shear moduli, even resulting in the total destabilization of a crystal structure [94,95], (ii) less prominent but still noticeable anomalies in short-wavelength phonon frequencies [92,93], and (iii), in thermodynamical properties of metals, heat capacity (see, e.g., [99] for Cd 1−x Mg x alloys) and thermal expansion. One result of the theory is the prediction of anisotropic thermal expansion for noncubic metals near an ETT at temperatures much lower than the Debye temperature.…”
Section: Hexagonal Close-packed Zinc Under Pressurementioning
confidence: 99%